2001
DOI: 10.1104/pp.126.1.261
|View full text |Cite
|
Sign up to set email alerts
|

ADP-Glucose Pyrophosphorylase Is Located in the Plastid in Developing Tomato Fruit

Abstract: The subcellular location of activity and protein of ADP-glucose pyrophosphorylase (AGPase) in developing tomato (Lycopersicon esculentum) fruit was determined following a report that the enzyme might be present inside and outside the plastids in this organ. Plastids prepared from crude homogenates of columella and pericarp, the starch-accumulating tissues of developing fruit, contained 8% to 18% of the total activity of enzymes known to be confined to plastids, and 0.2% to 0.5% of the total activity of enzymes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 28 publications
(6 reference statements)
4
33
0
Order By: Relevance
“…The regulation of starch synthesis has received much attention in tomato fruit (Beckles et al, 2001a(Beckles et al, , 2001b, and it has been reported that the reaction catalyzed by AGPase is the limiting step for starch biosynthesis in potato (Solanum tuberosum) tubers (Tiessen et al, 2002), a Solanaceae species close to tomato. Indeed, modifying AGPase activity and properties has a direct impact on starch levels in plants (Tsai and Nelson, 1966;Smidansky et al, 2002;Berger et al, 2004;Hädrich et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of starch synthesis has received much attention in tomato fruit (Beckles et al, 2001a(Beckles et al, , 2001b, and it has been reported that the reaction catalyzed by AGPase is the limiting step for starch biosynthesis in potato (Solanum tuberosum) tubers (Tiessen et al, 2002), a Solanaceae species close to tomato. Indeed, modifying AGPase activity and properties has a direct impact on starch levels in plants (Tsai and Nelson, 1966;Smidansky et al, 2002;Berger et al, 2004;Hädrich et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…All dicotyledonous plant AGPases studied thus far are plastidic proteins, whereas cereal endosperm AGPase is both cytoplasmic and plastidic (Beckles et al 2001;James et al 2003). The subcellular location and transit peptide sequences of the six sweet potato AGPase isoforms were mainly predicted using TargetP (http:// www.cbs.dtu.dk/services/TargetP/).…”
Section: Cloning and Analysis Of Sweet Potato Agpase Subunit Cdnasmentioning
confidence: 99%
“…The enzyme is now known to be largely extra-plastidial (i.e. 85-95%) in cereal endosperm, but plastidial in other cereal tissues and in all tissues of non-cereal plants [16,[26][27][28][29][30]. The starch-deficient kernel phenotypes of maize shrunken2 and brittle2 is caused by the loss of endosperm-specific cytosolic AGP-L and AGP-S isoforms, respectively, suggesting that plastidial AGPase by itself is not sufficient to support the normal processes of starch biosynthesis in cereal endosperm [31][32][33][34].…”
Section: Adp-glucose Pyrophosphorylase (Agpase)mentioning
confidence: 99%
“…It starts with individual chains as the first level, which are formed by ADP-glucose through (1→4)-α-glycosidic linkages. Those chains in amylopectin have been further denoted as C chains having the reducing end, A chains (degree of polymerization, DP, [6][7][8][9][10][11][12] carrying no branches, B1 chains (DP [13][14][15][16][17][18][19][20][21][22][23][24] carrying A chains, B2 chains (DP DOI 10.1515/amylase-2017-0006 [25][26][27][28][29][30][31][32][33][34][35][36] carrying B1 chains, B3 chains (DP > 36) carrying B2 chains, and so on (for a recent review, see [2]). Although still occasionally one finds statements to the contrary, amylose is not solely linear, but contains a small but significant number of long-chain branches [3].…”
Section: Introductionmentioning
confidence: 99%